(untitled) (Boletín Epidemiológico Semanal, 2025)
Introduction: Legionnaires’ disease is an infectious disease caused by inhalation of aerosols of water contaminated with the bacterium Legionella pneumophila. Although most cases are sporadic and community-acquired, its origin is usually unknown. The aim of the study was to describe the spatiotemporal distribution of autochthonous, sporadic and community-acquired cases in Spain between 2011 and 2023. Method: A descriptive spatiotemporal analysis of confirmed cases of legionellosis reported to RENAVE between 2011 and 2023 was performed, excluding imported, nosocomial, outbreak or travel-associated cases and Pontiac fevers. Incidence, mortality and case fatality rates were calculated at national level and by sex, age and province of residence of the patient. Results: 13,037 cases were reported. The average annual incidence rate was 2.17 per 100,000 inhabitants, with a predominance in men (71.9%) and over 65 years of age. An annual increase of 8.96% in incidence and 11.19% in mortality was observed, with marked seasonality between June and November. The provinces with the highest incidence were Gipuzkoa, Huesca and Cantabria. The case fatality rate was 6.18%. Discussion: There is an increase in the incidence and mortality rates of sporadic and community-acquired cases of legionellosis. The highest rates are concentrated in the northeastern region of the country, which may indicate an origin associated with environmental factors such as meteorology or land use. Differences in diagnosis and reporting between the different regions should be considered as a limitation of the study.